Effect of alumina-formers addition on the isothermal oxidation of TI-AL based intermetallics - Tan, Ming Jiun (2008)
The main objective of this study is to investigate the effect of adding the alumina former elements on the isothermal oxidation behavior of Ti-Al based intermetallics. High temperature oxidation test was carried out on Ti-Al based intermetallics namely the Ti-48Al-0.5Ag, Ti-48Al-2Cr-1.5Ag and Ti-48Al-2Cr- 1.5Ag-0.5W oxidized isothermally at 900Â°C. The kinetic rates of oxidation for the intermetallics were near to parabolic and the addition of Chromium (Cr) increased the kinetic rate of oxidation. Examination on the surfaces of oxide scales by using the Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy (AFM) and the X-ray Diffraction (XRD), revealed that the phases formed on the scale surfaces were dependent on the composition of the base alloy and the kinetic rates of oxidation. Analysis of the scale cross section found that the adherence of the scale to the base alloy improved by the addition of the alumina former elements. Based on the Energy Dispersive X-ray (EDX) spot and line scan analysis performed on the cross sectional of the scale, all the intermetallics showed an Al-depleted zone and the formation of aluminum oxide in the scale even at the early stage of the scale development. This indicated that the outward diffusion of aluminum to form Al2O3 is promoted by the addition of alumina former elements. Microhardness-indentation results revealed that the hardness values were different across the cross section of the scale. The hardness was the highest in the scale due to the presence of high TiO2 content.